Empowering communities through participatory monitoring and evaluation in Tororo district - Pali, Pamela N.; Nalukwago, G; Kaaria, Susan K.; Sanginga, Pascal C.; Kankwatsa, P (2005)
The Community Based Participatory Monitoring and Evaluation (CB-PME) tool empowers poor local farming communities to improve their livelihoods. While this process is people centred, it draws on local people’s capacities, while giving the end users of a technology a voice. The experience of the Katamata farmers’ group in Tororo district using PM&E is given in this paper. This group have embarked on a commercial groundnut production enterprise to improve their livelihoods. They decided to monitor one and three year-prioritized objectives for this enterprise. The three year objectives were based on the improvement of the farmers’ livelihoods and included having food security, with a marketed surplus, creating an awareness of HIV/AIDS, and individual commercial production, while the one year objectives dealt with the improvement in agricultural production. Some short term objectives have been achieved. The farmers have selected the best variety for commercial groundnut production. They have since reflected on these objectives and indicators with the monitoring and evaluation committee from their group whose main function is to collect, synthesize, store and report information to the group, community and visitors. This participatory process has empowered farmers to make production and marketing decisions on their enterprises and social lives with the ultimate goal of improving their livelihoods.